The complete mitochondrial genome of cricket Sclerogryllus punctatus (Orthoptera: Gryllidae) and phylogenetic analysis - Yu, Zheyuan; Xie, Huicong; Liu, Yijiao; Li, Kai; He, Zhuqing (Journal of Asia-Pacific entomology, 2022)
[Display omitted] •Mitochondrial genomes of Sclerogryllus punctatus were firstly sequenced and described.•The phylogeny of Sclerogryllus was inferred from mitogenomic data for the first time.•Phylogenetic results provided strong supports that Sclerogryllus is included in Gryllinae. The crickets of genus Sclerogryllus Gorochov, 1985 belongs to subfamily Sclerogryllinae of family Gryllidae. In this study, we report the first complete mitogenome sequences of the genus Sclerogryllus, and analyze the features of mitogenomes of S. punctatus. The mitogenome of S. punctatus was 15,438 bp and consisted of 37 genes, coding for 13 proteins, 2 ribosomal RNA (rRNA) and 22 transfer RNA (tRNA), and a control region. S. punctatus shares the arrangement of trnE-trnS-trnN with most mitogenomes of Grylloidea. Besides, the tRNAs possess the typical cloverleaf secondary structure except for the trnS1 (AGN) gene. The phylogenetic analysis using 13 protein-coding genes and 2 rRNA represents that genus Sclerogryllus is included in subfamily Gryllinae. Our results uncover the phylogenetic position of genus Sclerogryllus by mitogenome data within the family Gryllidae.